THE ISSUE OF RESTORATION OF ARCHITECTURAL MONUMENTS OF BUKHARA IN THE 20S OF THE XX CENTURY (Scientific journal of the Fergana State University, 2023)
This article, based on documents related to the activities of the organization Turkkomstaris, highlights the issue of restoration of architectural monuments in Bukhara in the 20s of the XX century. Information about the expedition organized for the protection and repair of historical monuments and their significance, attitude towards monuments, as well as the features of repair work during this period are presented.